GAYA HIDUP KONSUMEN DALAM PENGAMBILAN KEPUTUSAN PEMBELIAN - Hartati, Ajeng Sri; Hurriyati, Ratih; Widjajanta, Bambang (Journal of Business Management Education (JBME), 2017)
Objective – To describe and determine the influence of lifestyle on purchasing decisions.Design/methodology/approach – This type of research is descriptive and verfikatif with random sampling of 120 respondents. Data analysis technique used is a simple linear regression The design of this study is cross sectional method with a certain period of time.Findings – Based on research results by using simple linear regression analysis showed that there is positive lifestyles of consumers on purchasing decisions.Originality/value – The difference in this study lies in the object of research, study time, measuring tools, literature used, the theory used and the results of research. Keywords: Marketing, Consumer Behavior, Lifestyle Consumer Purchase Decision, Action Cameras, GoPro.Type Article: Research paper